Low-Dose Decitabine Assists Human Umbilical Cord-Derived Mesenchymal Stem Cells in Protecting β Cells via the Modulation of the Macrophage Phenotype in Type 2 Diabetic Mice - Jing Xue; Yu Cheng; Haojie Hao; Jieqing Gao; Yaqi Yin; Songyan Yu; Junyan Zou; Jiejie Liu; Qi Zhang; Yiming Mu (Hindawi Limited, 2020)
Background. Progressive β-cell dysfunction, a major characteristic of type 2 diabetes (T2D), is closely related to the infiltration of inflammatory macrophages within islets. Mesenchymal stem cells (MSCs) have been identified to alleviate β-cell dysfunction by modulating macrophage phenotype in T2D, but the restoration of β-cells by a single MSC infusion is relatively transient. Decitabine (DAC) has been reported to polarize macrophages towards the anti-inflammatory phenotype at low doses. We therefore investigated whether low-dose decitabine could enhance the antidiabetic effect of MSCs and further promote the restoration of β-cell function. Methods. We induced a T2D mice model by high-fat diets and streptozotocin (STZ) injection. Mice were divided into five groups: the normal group, the T2D group, the DAC group, the MSC group, and the MSC plus DAC group (MD group). We examined the blood glucose and serum insulin levels of mice 1, 2, and 4 weeks after MSC and/or DAC treatment. Dynamic changes in islets and the phenotype of intraislet macrophages were detected via immunofluorescence. In vitro, we explored the effect of MSCs and DAC on macrophage polarization. Results. The blood glucose and serum insulin levels revealed that DAC prolonged the antidiabetic effect of MSCs to 4 weeks in T2D mice. Immunofluorescence staining demonstrated more sustainable morphological and structural amelioration in islets of the MD group than in the MSC group. Interestingly, further analysis showed more alternatively activated macrophages (M2, anti-inflammatory) and fewer classically activated macrophages (M1, proinflammatory) in islets of the MD group 4 weeks after treatment. An in vitro study demonstrated that DAC together with MSCs further polarized macrophages from the M1 to M2 phenotype via the PI3K/AKT pathway. Conclusion. These data unveiled that DAC prolonged the antidiabetic effect of MSCs and promoted sustainable β-cell restoration, possibly by modulating the macrophage phenotype. Our results offer a preferable therapeutic strategy for T2D.